Costs, rewards and social reciprocity: Teachers' motivations for networked learning - van den Beemt, Antoine; Ketelaar, Evelien; Diepstraten, Isabelle; de Laat, Maarten (Proceedings of the International Conference on Networked Learning, 2014)
This paper discusses teachers' perceptions of learning networks and arguments for participating in these networks, viewed from a social exchange and symbolic interaction perspective. Although the use of learning networks to improve informal learning of teachers appears to be promising, teacher participation in informal networks is scarce. In this paper we try to find reasons for this scarcity by studying teachers' considerations for (non-) participation in learning networks. Central to this type of studies is the theme of reciprocity. Previous research approached reciprocity from a rational exchange perspective. We do an effort to extend this approach with elements from symbolic interactionism, aiming at an understanding of the relation between a) teachers' perceptions of learning networks, and b) considerations for participation in learning networks. Participation in learning networks does not only depend on a rational consideration of costs and rewards, but also on traditions and rituals because of belonging to a social order. We pursue our exploration, guided by the following research question: What is the relation between teachers' perceptions of learning networks, and their considerations for (non-) participation in these networks? We answer this question by means of data from structured interviews among 25 teachers in secondary education. The data show perceptions of learning networks as organised both inner-school and outside school, and mostly focused around specific content knowledge or themes. The considerations for (non-) participation range from costs, such as time and self-efficacy, to rewards such as useful content for lessons and contacts with others. In addition to these economic motives for participating in learning networks, we also found symbolic arguments for networking such as joy, sharing, mutual understanding and meaning giving resulting from the networking activities. The results led us to conclude that in addition to social exchange motives, symbolic aspects of communication and interaction play an important role in considerations for participation in (online) learning networks. The results of our exploration can be used to support the development of (informal) learning networks for teachers.